(untitled) (Numerus academy review, 2026)
This study aims to conceptualize the future diversification of Arab economies, , the study concluded that some Arab countries have made great strides towards diversifying their economies, and this is the allowance of the Gulf Cooperation Council, while the rest of the countries expect their dependence on a few sectors to remain unsustainable or uncompetitive due to continued political instability.